Searching for a “pedagogy of hope”: teacher education and the social sciences - Samuel, Michael (Faculty of Education, University of the Free State, 2010)
I analyse module outlines within a particular school of social sciences located in a faculty of education, and uncover the evolving systems of teaching social sciences in a teacher education curriculum. The data are analysed through two theoretical lenses: firstly, through the lense of models of teacher education and professional development, and secondly, through the lense of multicultural and multi disciplinary studies. The analysis reveals that a new language around social sciences is still in the early stages of development, drawing its main referencing from the official policy of the National Curriculum Statement. Unable to develop an independent new language, the social sciences in teacher education tend to capitulate to external dominant forces. There is little evidence of engaging with a critical discourse around the potential of teacher edu cation, resulting in a perpetuation of an applied science notion of professional growth. The juxta posing of existing disciplinary boundaries constitutes the character of the delivery of the social sciences. I point to a “pedagogy of hope” which focuses on the future rather than on the present status of marginalisation of the social sciences in a teacher education curriculum. The paper offers a way to develop a “Creole”, a language and a discourse around the social sciences in general, for teacher education in particular.
Keywords: Multi-cultural education; Multi-disciplinarity; Social sciences; Sociolinguistics; Teacher education curriculum; Teacher professional development